ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEPATUHAN WAJIB PAJAK DI KPP PRATAMA BATAM SELATAN - Roswini, Roswini; Wage, Sunarto (SCIENTIA JOURNAL, 2021)
Tax is already familiar and have become one of the provenance for country income, which is relied upon to become the buffer composition of the country's construction for realize the welfare of all indonesian people. However, the expected compliance rate is not comparable with what is realized and not 100% of registered taxpayers perform tax reporting. This riset was conduct to find the effect and significance of tax penalty and tax knowledge to tax compliance at KPP Pratama Batam Selatan. This study used purposive sampling technique with Slovin formula and an error tolerance of 5%, so got 400 respondents. The data was obtained through questionnaires and used SPSS application. The results is by partially or simultaneously that tax penalty and variable tax knowledge have positive influence and significant to taxpayer compliance. For X1, it is justified by tcount (4,476) > ttable (1,966), and significance’s value is 0,000 < 0,05. For X2, it is justified by tcount (4,480) > ttable (1,966), and the significance’s value is same with X1. In addition, the both variables was declared have positive effect and significant for Y variable, justified by the value of Fcount (179,772) > Ftable (3,02) with significance’s value 0,000 < 0,05.